Pengaruh penerapan LKS virtual laboratory dalam model pembelajaran problem solving terhadap kompetensi siswa kelas X di SMA Pertiwi 1 Padang - everly aberta; masril masril; hidayati hidayati; yenni darvina (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose of Indonesian education is to develop capabilities and shape dignified national character and civilization. In line with the objectives of Indonesian education, education today must be able to produce highly competitive human resources. The reality at school shows that there is still a low percentage of students in achieving the Minimum Completion Criteria set. The low student learning outcomes are caused by several factors, among others, the students' initial knowledge is less attention, the lack of teachers explaining real problems in daily life, teachers rarely involve students actively in problem-solving, and inadequate school laboratory facilities. The purpose of this study was to find out the influence of the use of the Virtual Laboratory Student Worksheet in the Problem Solving Learning Model on the competency of class X students at SMA Pertiwi 1 Padang. The type of research used was quasi-experimental with pretest and posttest. The sampling technique in this study used purposive sampling. The instrument for collecting data consists of written test sheets for knowledge competencies and performance assessment sheets for skills competencies. Data from the study were analyzed by analysis of two-way ANOVA. Based on data analysis it can be stated that the use of the Virtual Laboratory Student Worksheet in the Problem Solving learning model has had a significant influence on the competency of the knowledge and skills of class X students at SMA Pertiwi 1 Padang. The conclusion of the results of this study is that there is a significant effect of the application of virtual laboratory Student Worksheet in the problem-solving learning model towards the competency of class X students of SMA Pertiwi 1 Padang.